Immobilization of horseradish peroxidase onto kaolin by glutaraldehyde method and its application in decolorization of anthraquinone dye - Šekuljica Nataša Ž.; Prlainović Nevena Ž.; Jovanović Jelena R.; Stefanović Andrea B.; Grbavčić Sanja Ž.; Mijin Dušan Ž.; Knežević-Jugović Zorica D. (Hemijska Industrija, 2016)
The problem of environmental pollution day by day becomes more worrisome, primarily due to the large amounts of wastewater contaminated with various harmful organic compounds, discharged into the environment untreated or partially clean. Feasibility of use of horseradish peroxidase (Amoracia rusticana) in the synthetic dyes decolorization was approved by many researchers. Among a number of supports used for the immobilization, it was found that natural clay, kaolin has excellent features which are a precondition for obtaining biocatalysts with the excellent performances. For this reason, a horseradish peroxidase was immobilized onto kaolin using glutaraldehyde as a cross-linking agent. Obtained biocatalyst was applied in the decolorization of anthraquinone dye C. I. Acid Violet 109. Under determined optimal conditions (pH 4.0, hydrogen peroxide concentration 0.6 mM, dye concentration 30 mg L-1, temperature 24ºC) around 76 % of dye decolorization was achieved. Reusability study showed that resulting biocatalyst was possible to apply four times in the desired reaction with relatively high decolorization percentage. [Projekat Ministarstva nauke Republike Srbije, br. III-46010 i br. 172013]